The Relationship of Insomnia and TCM Constitution in Huachiew Chalermprakiet University Students - Lin ํYusheng; Go , Sungteak; Mahadilokrat, Orakoch (Journal of Health Sciences and Wellness, 2022)
Insomnia is the most common related health problem, which affects memory, creativity, and ability to learn. This research will study the relationship of insomnia and the Traditional Chinese Medicine (TCM) Constitution in groups of 113 Huachiew Chalermprakiet University students by using questionnaire data collection. Information was randomly collected from each class of students who filled in the questionnaires by themselves. These questionnaires include general personal information and health awareness assessment forms such as general health assessment questionnaires, stress assessment form, Pittsburgh Sleep Quality Index (PQSI), and TCM constitution questionnaire to analyze the relationship of people with insomnia and the basics of physical health according to TCM among students. Aim to refer to further teaching and guidelines for students with insomnia. The results of the study showed the relationship between TCM constitutions of the sample and the quality of sleep was significant (F= 2.196, p=0.013) and the top 5 groups most likely to have insomnia or having poor sleep quality had Qi-deficiency, Special, Qi-depression, Yin-deficiency, and Dampness-heat constitutions, while the balanced constitution had relatively good sleep quality. Also, it was found that the special constitution group was top-ranked for insomnia, which had never been seen in previous reviews of the literature. This may be due to different locations, which make everyone’s basics of physical health different.